2022
DOI: 10.1108/ijse-10-2021-0638
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of information and communication technology in reducing the gap between rich and poor: the case of South Asia

Abstract: PurposeThe widening income gap between rich and poor has gained worldwide recognition in recent decades. This income gap between rich and poor is defined as the extent of income unevenly distributed in a host country. This study provides an empirical view of the association between information and communication technology and the widening of the income gap.Design/methodology/approachThe study used panel data from 2005 to 2019. To detect unit root issues, Levin and Lin (LL) and Im, Pesaran and Shin (IPS) tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Los resultados anteriores coinciden con los encontrados en Neal (2013), Adams y Klobodu (2019) y Igwegbe y Amaka (2021), donde la contribución en la reducción de la desigualdad de ingresos por parte de las variables explicativas deja de ser estadísticamente significativa en el largo plazo. El uso del internet como variable proxy del uso de las Tecnologías de la Información y la Comunicación (TICs), continúa siendo estadísticamente significativo en el largo plazo, denotando el efecto dinámico positivo del uso de la tecnología en el crecimiento de los países analizados y en sus procesos de reducción de la desigualdad, tal como se evidencia en Tang et al (2022), Hafeez et al (2020), Ahmad et al (2022) y Alimi y Okunade (2020). Finalmente, respecto a las variables de control, se evidencia el aumento de la población urbana y de la producción per cápita provoca un aumento del nivel de desigualdad de ingresos de los países de la OCDE, corroborando la dificultad para reducir dicha desigualdad, aún en el caso de países más desarrollados, coincidiendo con lo mencionado en Adams y Klobodu (2019), Mishra y Agarwal (2019), Bahmani-Oskooee y Ardakani (2020) y Hailemariam et al (2021).…”
Section: Discusión De Resultadosunclassified
“…Los resultados anteriores coinciden con los encontrados en Neal (2013), Adams y Klobodu (2019) y Igwegbe y Amaka (2021), donde la contribución en la reducción de la desigualdad de ingresos por parte de las variables explicativas deja de ser estadísticamente significativa en el largo plazo. El uso del internet como variable proxy del uso de las Tecnologías de la Información y la Comunicación (TICs), continúa siendo estadísticamente significativo en el largo plazo, denotando el efecto dinámico positivo del uso de la tecnología en el crecimiento de los países analizados y en sus procesos de reducción de la desigualdad, tal como se evidencia en Tang et al (2022), Hafeez et al (2020), Ahmad et al (2022) y Alimi y Okunade (2020). Finalmente, respecto a las variables de control, se evidencia el aumento de la población urbana y de la producción per cápita provoca un aumento del nivel de desigualdad de ingresos de los países de la OCDE, corroborando la dificultad para reducir dicha desigualdad, aún en el caso de países más desarrollados, coincidiendo con lo mencionado en Adams y Klobodu (2019), Mishra y Agarwal (2019), Bahmani-Oskooee y Ardakani (2020) y Hailemariam et al (2021).…”
Section: Discusión De Resultadosunclassified
“…3) The results of the benchmark analysis in the same table indicated that the number of mobile and wireless lines is statistically morale and affects GDP by (2.04%) in the long term. [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30] 4) The Internet intensity index per 100 people was statistically moral and influenced GDP by 1.48% in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…This was because the features are too long and difficult to understand due to the use of formal, ambiguous language. Moreover, not all users come from economically well-off circles, which has an impact on ignoring the security of personal data when using e-commerce (Ahmad et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%